Comprehensive chemical profiling of two Dendrobium species and identification of anti-hepatoma active constituents from Dendrobium chrysotoxum by network pharmacology - Xia Jie; Yin Feng; Fang Jiahao; Lou Ganggui; Yu Jiani; Xu Zhongyu; Yuan Yuan; Zhang Tinggang; Zhang Xiaodan; Liang Zongsuo (BMC, 2023)
Abstract Background Dendrobium nobile and Dendrobium chrysotoxum are important species of the genus Dendrobium and have great economic and medicinal value. However, the medicinal properties of these two plants remain poorly understood. This study aimed to investigate the medical properties of D. nobile and D. chrysotoxum by conducting a comprehensive chemical profiling of the two plants. Additionally, active compounds and predictive targets for anti-hepatoma activity in D. chrysotoxum extracts were identified using Network Pharmacology. Results Chemical profiling showed that altogether 65 phytochemicals were identified from D. nobile and D. chrysotoxum, with major classes as alkaloids, terpenoids, flavonoids, bibenzyls and phenanthrenes. About 18 compounds were identified as the important differential metabolites in D. nobile and D. chrysotoxum. Furtherly, CCK-8 results showed that the extracts of stems and leaves of D. nobile and D. chrysotoxum could inhibit the growth of Huh-7 cells, and the anti-hepatoma activity of extracts were dose-dependent. Among the extracts, the extract of D. chrysotoxum showed significant anti-hepatoma activity. In order to find the potential mechanism of anti-hepatoma activity of D. chrysotoxum, five key compounds and nine key targets were obtained through constructing and analyzing the compound-target-pathway network. The five key compounds were chrysotobibenzyl, chrysotoxin, moscatilin, gigantol and chrysotoxene. Nine key targets, including GAPDH, EGFR, ESR1, HRAS, SRC, CCND1, HIF1A, ERBB2 and MTOR, could be considered as the core targets of the anti-hepatoma activity of D. chrysotoxum. Conclusions In this study, the chemical composition difference and anti-hepatoma activity of stems and leaves of D. nobile and D. chrysotoxum were compared, and the potential anti-hepatoma mechanism of D. chrysotoxum was revealed in a multi-target and multi-pathway manner.